Narodno-osvoboditelnaya vayna na severnom kavkaze pod predvoditelstvom şamilya i ee mejdunarodnoe znaçeniye : Mejdunarodnaya naukaya konferançiya posvaşennaya 200 lemiyo so bnya rojdeniya imama şamilya 21-22 oktyabıya 1977 = North caucasian peoples war of liberation under leadership of shamil its international importance international scientific conference dedicated to the 200th anniversary of İmam Shamil (Mahaçkale)
19 s.